PENGARUH MOTIVASI MENGAJAR GURU DAN KETERAMPILAN MENGAJAR GURU TERHADAP HASIL BELAJAR SISWA SMA NEGERI DI KOTA BUKITTINGGI - Fajar Budiman; Agus Irianto (Program Magister Pendidikan Ekonomi (S2), 2015)
This study aims to look at the influence of teachers' motivation and teaching skills of teachers on student learning outcomes. Approach is used in this study is ekplanatif. the number of samples from a population of 276 163 high school teachers in the country town Bukittinggi. Data collection for the motivation to teach teachers and teachers' teaching skills using a scale of twigs, while the student learning outcomes derived from the value that has been documented by the teacher. Data analysis technique using path analysis. Research findings that affect the motivation of teachers to teach students learning outcomes and teaching skills of teachers not significant effect on student learning outcomes. Key words: Motivation to Teach Teachers, Teaching Skills of Teachers, Student Learning Outcomes